Trust in virtual teams: a performance indicator - Nakayama, Marina Keiko (2006)
This paper aims to analyze how virtual teams deal with the process of trust among the people who are part of it. The research is characterized as descriptive. The survey data techniques that were used were questionnaires via Internet and interviews by telephone. The participants of this research were eight managers from Embratel, a telecommunication company in Brazil. The results of this research pointed out that, for its participants, trust is a significant performance indicator for the collaborators and that reciprocity, positive expectation and foresight are base concepts so that all may feel secure when it comes to the risk of a negative consequence and vulnerability. The clear definition of the objectives, the emphasis in internal communication, the manager as an example and model, and the worthiness of the people become the main care and practice in order to obtain better trust in virtual teams.